Hydrophytes In The High Barind Tract: Diversity Status Threats And Conservation - Begum, Syeda Salma (Journal of the Asiatic Society of Bangladesh, Science, 2014)
A survey was conducted to assess the diversity of hydrophytes in some selected locations including Kharoil Beel (Mohanpur), Beel Kumari (Tanore) and Jobai Beel (Sapahar) situated in High Barind Tract, Rajshahi, Bangladesh from June 2005 to May 2008. Among them Jobai Beel is the largest, Beel Kumari is medium and Kharoil Beel is small in size. At experimental areas a total of 151 plant species and 90 genera distributed in 44 families was identified. From the result, diversity status of the study areas, the values ranged between 0.94-0.97 in Simpson’s index and 3.55-4.13 in Shannon’s index. Diversity status of three study areas shows richness. Sequence of richness is as follows- Kharoil Beet> Beel Kumari > Jobai Beel. It is also evident that these wetlands are disturbed by anthropogenic activities. Some of the species have become threatened, some have become rare. Conservation efforts and awareness building are perquisite for the sustainability of these wetlands Asiat. Soc. Bangladesh, Sci. 40(2): 259-270, December 2014